(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
Ginger is one of the most widely distributed spices grown in various cropping systems and locations throughout the southwestern Ethiopia. Bacterial wilt, caused by Ralstonia solanacearum, is one of the serious diseases of ginger in Ethiopia. Field experiments were conducted during 2019 and 2020 to assess effects of soil amendments on bacterial wilt development and epidemics at Tepi, Ethiopia. Three soil amendments practices: compost, effective microorganisms and Bordeaux mixture alone and in integration were evaluated. Treatments were arranged in a randomized complete block design with three replications. Compost at the rate of 7 ton ha-1 enriched with effective and Bordeaux mixture treatment significantly reduced ginger bacterial wilt severity, AUDPC and disease progress rate. This treatment reduced bacterial wilt mean severity by up to 21.08% as compared to untreated control plot. Compost at the rate of 7 ton ha-1 application also slowed down epidemic progression of bacterial wilt and significantly reduced the disease parameters when integrated effective microorganisms and Bordeaux mixture. The overall results indicated that integrated compost enriched with effective microorganisms and Bordeaux mixture was effective to slow down the epidemics of bacterial wilt and to sustain ginger production and productivity. Hence, integrated compost enriched with effective microorganisms and Bordeaux mixture along with other crop management systems are recommended for improved ginger production and productivity. Int. J. Agril. Res. Innov. Tech. 12(1): 72-78, June 2022